The Organizational Perspective Model: A Study in PT Starqle Indonesia - Chandra, Albert Tommy Tanggo; Tjakraatmadja, Jann H. (Universitas Prasetiya Mulya, 2011)
Balancing creativity and structure becomes an emerging issue, especially for companies whose competitive advantage is on creativity because failure in managing both creativity and structure will result in business losses, as experienced by Netscape, Xerox and Microsoft. PT Starqle Indonesia tends to experience the imbalance condition between creativity and structure, especially when the company plans to change its business focus from project-based to product-based. In project-based, structure is more emphasized. While to anticipate the business changing, Starqle must be able to manage both creativity and structure. The influence factors are company lifecycle, competency, ownership, self-motivation, leaders, and trust, while for structure; these factors are business process, organizational structure and policy. Builtto-change approach is used to balance both creativity and structure as continuous process. The approach focuses on 3 (three) core components: strategizing, creating value and implementing. Strategic intent should be aligned with identity to strengthen the creativity side. Creating value by leveraging learning is performed to improve the structure by means of conducting knowledge activity cycle to capture individual process in generating new knowledge. The last component i.e implementation is to improve creativity and structure by focusing on people, process and information technology.